The correlation between learners' proficiency levels and their use of communication strategies : - Lê, Tấn A (Trường Đại học Cần Thơ, 2010)
The present study aims to explore wether there is any correlation between learners' proficiency level and the communication strategy use of English learners' in a university in Mekong Dalta. The study first attemps to investigate the reports of the frequency of CS use by high-proficient students and low-proficient students. The study then examines whether there is any correlation between students' use of communication strategies proficiency level.